2020
DOI: 10.3390/plants9030368
|View full text |Cite
|
Sign up to set email alerts
|

Non-Destructive Detection of Tea Leaf Chlorophyll Content Using Hyperspectral Reflectance and Machine Learning Algorithms

Abstract: Tea trees are kept in shaded locations to increase their chlorophyll content, which influences green tea quality. Therefore, monitoring change in chlorophyll content under low light conditions is important for managing tea trees and producing high-quality green tea. Hyperspectral remote sensing is one of the most frequently used methods for estimating chlorophyll content. Numerous studies based on data collected under relatively low-stress conditions and many hyperspectral indices and radiative transfer models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 83 publications
(106 reference statements)
4
33
0
Order By: Relevance
“…These results suggested that the inclusion of YL, which had the lowest Chl content in the dataset, functioned well at estimating the Chl content, but not the N content. Furthermore, these results indicated that the approach using hyperspectral reflectance and machine learning algorithm allowed not only the Chl content, as previously reported by Sonobe et al (2020) 54 , but also the N content to be estimated nondestructively in tea leaves. For green tea production, especially in Japan, N fertilizer is mainly applied in the autumn, winter, and at the bud-opening stage before the first crops in spring, to improve the quality 55 .…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…These results suggested that the inclusion of YL, which had the lowest Chl content in the dataset, functioned well at estimating the Chl content, but not the N content. Furthermore, these results indicated that the approach using hyperspectral reflectance and machine learning algorithm allowed not only the Chl content, as previously reported by Sonobe et al (2020) 54 , but also the N content to be estimated nondestructively in tea leaves. For green tea production, especially in Japan, N fertilizer is mainly applied in the autumn, winter, and at the bud-opening stage before the first crops in spring, to improve the quality 55 .…”
Section: Discussionsupporting
confidence: 84%
“…A stratified sampling approach for modelling was repeated 100 times to obtain robust results. tea leaves also indicated that the values of highest importance were confirmed at 700-750 nm (the red edge region) when OR and FDR were used 54 . For N content, the peaks of importance were observed at 675-725 and 1325-1575 nm, with the latter peak in the near-infrared region enhanced in DatasetB compared with DatasetA, especially for RF, Cubist, and SGB (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…As such, the variations in the total chl:car ratio [8] or chl a:car ratio [9] have been used for evaluating environmental stress in plants. In agriculture, the controls of nutritional condition, pH, or light conditions have been conducted to improve the appearance or quality of products [10][11][12]. However, these treatments sometimes lead to the early mortality of plants due to excessive environmental stress [13].…”
Section: Introductionmentioning
confidence: 99%